How can Collection of Wild Edible Fungi Contribute to Livelihoods in Rural Areas of Nepal? (Journal of Forest and Livelihood, 2005)
Collection of wild edible fungi is important for livelihoods in rural areas of Nepal and neighbouring countries. Only very few species of fungi are being exported from Nepal, and compared to neighbouring countries there is still a potential to be exploited. However, a system of quality control and training of local people must be considered to use this potential. Also, a better understanding of the ecology and management of the wild edible fungi is necessary for the development of a sustainable use of the resource.